Properties of Cement Sand Brick Containing Shredded Paper as Partial Sand Replacement - Bin Azuwa, Solahuddin (Salehan Institute of Higher Education, 2026)
Sand disposal causes significant environmental pollution. Effective sand mining is one of the alternative approaches to reduce sand disposal. Thus, this research investigates the properties of cement sand brick (CSB) containing shredded paper (SP) at various percentages, 0%, 10%, 20%, 30%, 40%, and 50%, as partial sand replacements. This research also investigates the mechanical and durability properties of CSB containing SP. The compressive, flexural, and splitting tensile strengths incline with 10 and 20% sand replacements with SP, respectively. 50% SP replacement shows the maximum influence on water absorption and efflorescence. The scanning electron microscope (SEM) elucidates that the emergence cracks are repaired, which improves the CSB’s strength by enhancing the bond connection between sodium hydroxide (Na(OH)2) and potassium-silicate-hydrogen (K-S-H) links. Some cement particles have been hydrated at 20% SP replacement, producing the highest strength. This study indicates that SP can be utilized as partial sand substitution in CSB at 10% and 20%, with significant improvements in strength and engineering properties, especially in building construction. Research on other types of SP that might yield stronger CSB is necessary for future research. Besides that, future studies shall investigate and observe the effects of CSB reactions with different percentages of SP usage.